Pemberdayaan Masyarakat Desa Daleman Kidul Melalui Rumah Sampah Digital Nawasena Kemala - Budi Hartono; Yenny Reiza Fitriana; Salsabila Nur Hapsari; Nadia Syakina; Fahar Kartiko Kuncoro Jati (Aspirasi Masyarakat, 2024)
Waste management in Daleman Kidul Village, Pakis District, Magelang Regency, is not yet optimal even though there are waste banks in three hamlets. The main problem is the lack of systematic and integrated institutions and low community participation in waste management. Therefore, the PPK Ormawa HMJM FE Program seeks to form the “Nawasena Kemala” institution as a village-level Digital Waste House that focuses on managing organic and inorganic waste. Through empowering PKK mothers, youth of Karang Taruna, and village residents, this activity develops skills in processing waste into products with economic value. As a result, villagers in eight hamlets are able to manage waste effectively through digital applications and contribute to improving the local economy. This program has succeeded in increasing environmental awareness and community education through sustainable activities.